Reframing Islamic Ecology as a Transformative Ethical Paradigm: Khalīfah, Tawḥīd, Mīzān, and the Global Ecological Crisis - Widiawaty; Uswatun Hasanah; Nyimas Umi Kalsum (CV. Jalan Cendikia, 2026)
The global ecological crisis requires an ethical response that goes beyond technical solutions and addresses theological, moral, and institutional dimensions. This study aims to reconstruct Islamic ecological principles as a transformative ethical paradigm for responding to contemporary environmental degradation. Using a conceptual-normative literature review and thematic analysis of Islamic normative sources and recent academic literature, this study examines the interconnection among tawḥīd, khalīfah, amānah, mīzān, fasād, isrāf, tabdhīr, and ḥifẓ al-bī’ah. The main finding shows that Islamic ecology is not a collection of isolated moral messages, but a theocentric and responsibility-centred paradigm that links worldview, human agency, ecological limits, consumption ethics, justice, and institutional praxis. The study implies that Islamic environmental discourse should move beyond doctrinal affirmation toward practical integration in Islamic education, pesantren and mosque governance, public policy, and community-based ecological movements.